2017
DOI: 10.1016/j.ijpharm.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Cancer therapeutics with epigallocatechin-3-gallate encapsulated in biopolymeric nanoparticles

Abstract: With the recent quantum leap in chemoprevention by dietary products, their use as cancer therapeutics is garnering worldwide attention. The concept of effortlessly fighting this deadly disease by gulping cups of green tea or swallowing green tea extract capsules is appreciated universally. Epigallocatechin-3-gallate (EGCG), a major polyphenol in green tea, has generated significant interest in controlling carcinogenesis due to its growth-inhibitory efficacy against a variety of cancers by targeting multiple si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Direct attachment to the surface, encapsulation of the polyphenol (with the option of co-encapsulation with other compounds), or incorporation within the surface of the nanoparticle are examples of methods used to associate nanoparticles with polyphenols. Nanoparticles have been used to increase the efficacy of EGCG as a targeted cancer therapeutic [157,158]. EGCG compounds alone can induce apoptosis and inhibit proliferation of cancer cells, although sometimes at doses that are not physiologically possible.…”
Section: Bioavailability Of Natural Compoundsmentioning
confidence: 99%
“…Direct attachment to the surface, encapsulation of the polyphenol (with the option of co-encapsulation with other compounds), or incorporation within the surface of the nanoparticle are examples of methods used to associate nanoparticles with polyphenols. Nanoparticles have been used to increase the efficacy of EGCG as a targeted cancer therapeutic [157,158]. EGCG compounds alone can induce apoptosis and inhibit proliferation of cancer cells, although sometimes at doses that are not physiologically possible.…”
Section: Bioavailability Of Natural Compoundsmentioning
confidence: 99%
“…In the past few years, green tea and its major polyphenol, catechin have been demonstrated to superior chemoprevention activity on multiple cancer types mainly because of their antioxidant/pro-oxidant properties (Naponelli et al, 2017). To improve the drug's bioavailability, stability, and tumor selectivity, nanotechnology-based drug delivery systems have been widely studied (Tyagi et al, 2017). To study the chemoprevention efficacy of combination, gold-conjugated green tea NPs were designed that demonstrated selective toxicity towards Ehrlich's Ascites Carcinoma and breast cancer cells MCF-7 and interestingly had hepatoprotective behavior against the tumorinduced cellular damage (Mukherjee et al, 2015).…”
Section: Miscellaneous Cancersmentioning
confidence: 99%
“…Co-treatment of EGCG with piperine (from black pepper) enhances the bioavailability of EGCG by 1.3-fold in mice (73). Several studies have demonstrated that encapsulation of EGCG inside a po lymer matrix, such as chitosan-based nanocarriers, improves its pharmacokinetics and pharmacodynamics (74). Hence, the potential of EGCG in clinical applications is boosted by these technologies.…”
Section: Stability and Bioavailability Of Egcgmentioning
confidence: 99%